2014
DOI: 10.1002/ehf2.12020
|View full text |Cite
|
Sign up to set email alerts
|

Altered myocardial force generation in end‐stage human heart failure

Abstract: Aims This study aimed to elucidate the molecular background of increased Ca 2+ sensitivity of force production in cardiomyocytes of end-stage human heart failure.Methods and results Ca 2+ -activated isometric force and the cross-bridge specific rate of force redevelopment (k tr ) were determined in Triton-skinned myocytes from end-stage failing and non-failing donor hearts. Measurements (control: pH 7.2, 0 mM inorganic phosphate (P i )) were performed under test conditions that probed either the Ca 2+ -regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…2D (square symbols). In line with several previous studies, Ca 2+ modulates kTR in same direction as force (26,28,30,32,(53)(54)(55)(56), i.e. in opposite direction to the Pi-modulated kTR-force relation.…”
Section: Dependence Of Force and K Tr On The [P I ]supporting
confidence: 92%
See 1 more Smart Citation
“…2D (square symbols). In line with several previous studies, Ca 2+ modulates kTR in same direction as force (26,28,30,32,(53)(54)(55)(56), i.e. in opposite direction to the Pi-modulated kTR-force relation.…”
Section: Dependence Of Force and K Tr On The [P I ]supporting
confidence: 92%
“…The rate constant kTR of this mechanically-induced force redevelopment represents the sum of apparent rate constants in the cross-bridge cycle limiting the transitions of cross-bridges between non-force-generating and force-generating states (26), reviewed in (2). There is consensus in several studies on slow and fast skeletal and cardiac muscles that Pi increases kTR whereas it decreases force (7,16,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The opposing effects of Pi on kTR and force are in line with the reversibility of Pi release and the force-generating step in muscles contracting under mechanical load, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the failing heart changes in the SR calcium cycling and also in myofilament, mechanics are described . This could influence the adaption to mechanical load also.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of heart failure on cells from the LV and RV is also unclear. Although numerous studies have shown that heart failure reduces maximum force and increases the calcium (Ca 2+ ) sensitivity of contraction of the permeabilized LV myocardium ( 4 , 5 , 6 , 7 , 8 , 9 , 10 ), few experiments have been performed using human RV samples. One recent study by Hsu et al.…”
mentioning
confidence: 99%